Data Exfiltration of Ultrasonic Signal in Computer Security System: A Review - Farah H. A. Jabar; Janatul Islah Mohammad; Ahmad Faizal Mohd Zain; Abu Bakar Hasan (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
It is crucial for public users and service providers to stay abreast of the progress and trends on data exfiltration in computer security system. In cryptosystem, it is unnoticeable for computer and mobile users to realize that inaudible sound used to transmit signals carrying pervasive sensitive data was in the low frequency ultrasonic range. Acoustic attacks on ultrasonic signal emanated by electronic devices have long been investigated among researchers. This paper is an exploration on the practicality of ultrasonic data exfiltration between computers in term of computer security system. It will discuss some work done by previous researchers in general, based on scientific, technological, and security perspectives. There will be inclusions of practical applications already in existence as well as future studies in related fields.